TASLIMA NASREEN’S PROTEST THEME - Shyam Narayan Singh (International Journal of Multidisciplinary Research and Studies, 2021)
Taslima Nasrin's Lajja is her magnum work; in it, she tackles a wide range of challenges that Bangladeshi nationalism is confronted with in the present day. The connection that has been made between religious identification and national identity has resulted in the formation of the postulate that everyone who is not a Muslim is an adversary, an alien, and someone who does not belong in Bangladesh. This has resulted in the growing isolation of the inhabitants of the Hindu minority from the cultural landscape in Bangladesh, preventing them from enjoying any advantage that comes with being a citizen of that country. As shown by the Dutta family in the film "Lajja," the Hindu populace is devastated when faced with the shocking reality of being ostracised by an ethnic group due to religious beliefs. Taslima Nasreen is a writer, feminist human rights activist, and secular humanist who hails from Bangladesh and writes in Bengali. She was raised in a Muslim household from the middle class in the north of Bangladesh in 1962, and she obtained a liberal education. She began her career as a physician in the less developed regions of her nation when she was 23 years old and had just become a doctor. When she first came to the notice of Westerners, she had already established herself as a prolific writer for many journals.